IMPLEMENTATION OF AUTHENTIC ASSESSMENT OF PSYCHOMOTOR DOMAIN IN PAI LESSONS ON TABLIGH MATERIAL CLASS XI RPL TAMANSISWA SUKADAMAI - Sirait, Azyana Alda; Nasution, Indah Widya Jaya Putri; Febrian, M Agil; Nurmawati, Nurmawati (Reflektika, 2025)
This study aims to analyze the implementation of authentic assessment in the psychomotor domain in Islamic Religious Education learning with Tabligh material in class XI RPL SMK Tamansiswa Sukadamai. This study uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation of teachers, students, and principals. Analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study showed that authentic assessment based on practice, such as group division, discussion, and presentation, was effective in improving students' ability to convey Islamic messages persuasively and politely. The assessment was carried out using instruments that included mastery of the material, delivery techniques, appropriateness of the content, and student performance. The obstacles faced included students' nervousness and lack of mastery of the material. In conclusion, authentic assessment can improve students' psychomotor skills, but requires support in the form of teacher training, improved facilities and infrastructure, and adaptive learning strategies. The 3F principle-based approach (Fun, Fresh, Focus) creates an interesting and relevant learning atmosphere to students' needs in the era of digital transformation.